219 A SOLITARY AWARENESS - PROFILING TIME TO RECOGNITION OF MEMORY LOSS IN A TERTIARY MEMORY SERVICE. (25th October 2022) - McHale, C; Dookhy, J; Dolphin, H; Fallon, A; O'Toole, R; Merron, G; Kennelly, S
Abstract: Background: Approximately 64, 000 people live with dementia in Ireland with expected increases to 150, 000 by 2045. Best practice recommends that patients benefit from timely diagnosis. Whilst the presence of cognitive impairment should prompt early referral for diagnostic clarity, patients frequently present with well-established symptoms. In order to understand this phenomenon it is important to understand the way in which symptoms are recognised by the person, companions and casual observers. Methods: A chart review was carried out on a convenience sample of patients (n=61) diagnosed with dementia where scores were available from Clinical Dementia Rating Scale (CDR) and AD8. Data extracted included global scores and answers to direct questions regarding symptom recognition by patient and companion. Diagnosis was confirmed using the Electronic Patient Record. Results: Mean age was 75 (range 57-87). Diagnostic breakdown comprised: Alzheimer Dementia (AD) in 67% (n=41), mixed AD/Vascular Dementia (VaD) in 19.6% (n=12); behavioural variant Fronterotemporal Dementia (bvFTD) in 1.6% (n=1), Dementia with Lewey Bodies (DLB) in 1.6% (n=1), Primary Progressive Aphasia (PPA) in 4.9% (n=3), Primary Parkinson's Dementia (PPD) in 1.6% (n=1) and VaD in 1.6% (n=1). Average CDR Global Scale was 1.0 and average AD8 score 6/8. Family noticed symptoms of dementia an average of 12 months longer than the person themself. The incidence of anosognosia was 19% (n=12) and associated with a diagnosis of AD (91.6 %, n=11). Where anosognosia existed, symptoms of memory loss had been identified by family up to 60 months before diagnosis, with average time to recognition of 24 months. For 75% of this anosognosia group, family reported indiscernible symptoms on casual inspection (n=9). Conclusion: Where symptoms of memory loss go unrecognised by patients and casual inspection, family may notice changes for up to five years. It is important to educate and empower the public regarding the benefit of a timely dementia diagnosis. Education should focus on supporting family to navigate sensitive conversations in the event of anosognosia and explore ways in which they might encourage timely review.